Sharks and rays have the oldest vertebrate sex chromosome with unique sex determination mechanisms - Taiki Niwa; Yoshinobu Uno; Yuta Ohishi; Mitsutaka Kadota; Naotaka Aburatani; Itsuki Kiyatake; Daiki Katooka; Michikazu Yorozu; Nobutaka Tsuzuki; Atsushi Toyoda; Wataru Takagi; Masaru Nakamura; et al. (Proceedings of the National Academy of Sciences, 2025)
Sex determination has been investigated across vertebrate lineages to reveal the stepwise evolution of sex chromosomes and the diversity of responsible molecular mechanisms. However, these studies rarely include cartilaginous fishes, which diverged from the other vertebrates 450 Mya, hindering the comprehensive view of vertebrate sex determination. Here, we produced chromosome-scale genome assemblies of egg-laying shark species and comparatively investigated genome sequences and transcriptome profiles across diverse cartilaginous fishes. Sex chromosome identification, supported by cytogenetic experiments, elucidated the homology of X chromosomes between sharks and rays as well as an extensively degenerated Y chromosome harboring no detectable male-specific genes. Orthologs of documented sex-determining genes were identified, but not on these sex chromosomes. Transcriptomic analyses combined with histology of embryonic gonads revealed female-biased expression of X-linked genes—including those implicated in the TGF-β and IGF signaling pathways—attributed to incomplete dosage compensation. Our findings indicate that sharks and rays share the oldest sex chromosomes among vertebrates that originated around 300 Mya and the dosage-dependent sex determination mechanism composed of distinct molecules from other vertebrates. This study highlights the antiquity of sex chromosomes and the uniqueness of sex determination mechanisms in sharks and rays, which advances our understanding of evolutionary plasticity in vertebrate sex determination.